2018
DOI: 10.1177/0047287518778148
|View full text |Cite
|
Sign up to set email alerts
|

Cruise Line Customers’ Responses to Risk and Crisis Communication Messages: An Application of the Risk Perception Attitude Framework

Abstract: The main purpose of this study was to test cruise line customers' responses to risk and crisis communication messages addressing health-related incidents on cruise ships. This study used norovirus infections as the context and the Risk Perception Attitude framework as the conceptual foundation. An experiment was conducted to test how communication messages affected cruise line customers' information search behavior, safety perceptions, and cruise travel intentions. A total of 240 responses were included and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 72 publications
(152 reference statements)
2
109
0
Order By: Relevance
“…As far as we know, no previous studies have focussed on how COVID-19 could affect consumer intention to cruise. Our paper therefore, adds to the relatively limited research on the effects of health-related risk perceptions associated with emerging crisis issues on individuals' evaluation of their perceived safety and their consequent intention to purchase a cruise (Liu et al, 2016;Liu-Lastres et al, 2019). Secondly, the study advances crowding literature in the cruise industry context, in which space and human interactions could be very critical.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As far as we know, no previous studies have focussed on how COVID-19 could affect consumer intention to cruise. Our paper therefore, adds to the relatively limited research on the effects of health-related risk perceptions associated with emerging crisis issues on individuals' evaluation of their perceived safety and their consequent intention to purchase a cruise (Liu et al, 2016;Liu-Lastres et al, 2019). Secondly, the study advances crowding literature in the cruise industry context, in which space and human interactions could be very critical.…”
Section: Introductionmentioning
confidence: 83%
“…We have also inserted two control variables in the model, namely, familiarity and past cruise experience. Given that Milman and Pizam (1995) suggested that travel experience is linked to familiarity, which might consequently reduce the perceived risk level and that the relationship between passengers' past cruise travel experience and cruise ships' safety perceptions has already been identified (Liu-Lastres et al, 2019), some differences in consumers' intention to cruise might result from the mentioned variables.…”
Section: Self-confidencementioning
confidence: 99%
“…Safety compliance involves compliant behavior consistent with institutional norms, position responsibilities, and specific task requirements, and safety participation is proactive behavior that contributes to developing an environment that supports safety (Newaz et al, 2019;Smith et al, 2019). However, hospitality companies encounter diverse and complex safety issues due to the risks from multiple external and internal factors (e.g., terrorist attacks, crimes, diseases, colleague rule-breaking, and customer behavior) (Kubickova et al, 2019;Liu-Lastres et al, 2019;Lugosi, 2019). Therefore, hotel managers and staff must be increasingly adaptable, versatile, and creative in solving threats and issues to ensure safety.…”
Section: Safety Behaviormentioning
confidence: 99%
“…Third, the moderation role of perceived risk in the influence of safety leadership has not been explored. Crisis events force people to make judgements and risk evaluations under pressure, and then serve as the foundation for behavioral decisions (Liu-Lastres et al, 2019;. Safety behavior decisions during crises and high-risk situations involve perceptions and evaluations of the risk environment (Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Safety communication aimed at image repair is exemplified in product recalls during product harm crises (Gao, Xie, Wang, & Wilbur, 2015). In tourism research, scholars have mainly investigated safety communication as an image repair mechanism after crises such as infection outbreak (Liu-Lastres, Schroeder, & Pennington-Gray, 2018), natural disasters (Chew & Jahari, 2014), and terrorism (Sönmez et al, 1999). Safety communication in these crisis contexts has the objective to assuage tourists and repair the negative image of a destination.…”
Section: Safety Communication Risk Propensity and Self-efficacymentioning
confidence: 99%